Analisis Sentimen Ulasan Google Play pada Aplikasi Tahu Sumedang Menggunakan Lexicon-Based - Sidik, Khairil; Dody Herdiana; M. Agreindra Helmiawan; Asep Saeppani (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
This study examines user perceptions of the Tahu Sumedang application based on reviews submitted on the Google Play Store. The purpose of this research is to identify user sentiment and understand the aspects that influence positive and negative evaluations of the application. The lexicon-based sentiment analysis method is used to classify each review into sentiment categories through a dictionary of words with positive and negative polarity. The results show variations in user sentiment that reflect satisfaction with certain features and concerns about technical performance, navigation, and application stability. The findings highlight several aspects that require improvement to optimize the quality of digital public services. The conclusion of this study emphasizes the importance of user feedback as an evaluation basis for developing more responsive and efficient public service applications.